Thermostable lipases: an overview of production, purification and characterization - Salihu, Aliyu; Alam, Md Zahangir (Oriental Scientific Publishing Company, 2014)
Thermostable lipases occupy a prominent position in aqueous and non-aqueous biocatalysis. Isolation of wild strains with novel properties has been on-going and recombinant strains are being constructed so as to meet the biotechnological applications of lipases. Different purification methods prove effective and the purity of the enzyme is dependent on the intended applications. Unlike medical and pharmaceutical applications where highly pure preparations are needed, partial purification can be sufficient for general applications. Thus, characterization associated with enzyme activity, specificity, thermostability, enatioselectivity and tolerance to various solvent systems are the prerequisite for thermostable lipase selection which make them highly demanding in lipase catalyzed reactions. This article intends to give an insight on thermostable lipases so as to stimulate researchers to explore other unique properties from wild and recombinant strains that could be of benefit for wider industrial applications.